English phraseological units denoting deception (cognitive aspect) - Kartun, Nataliia (Видавничий дім "Гельветика", 2022)
Being a complicated interweaving of intentional, cognitive, and moral aspects, deception accompanies human communication and is realized in it. Deception as a concept is a component of the conceptual picture of the world and linguistic, in particular, phraseological means of objectifiation of this concept create a linguistic picture of the world. The relevance of the research subject is determined by the great signifiance of the concept of DECEPTION, objectifid by the analyzed phraseological units for the English-speaking community, by the correspondence to the major directions of modern linguistic research, and by the need to identify the cognitive basis of phraseological units denoting deception for the reconstruction of conceptual and linguistic picture of the world. The article considers a cognitive aspect of the analysis of phraseological units denoting deception. The core of the phraseological units denoting deception was systematized and the specifiity of phraseological units denoting deception in the cognitive aspect was defied. The analysis of the phraseological units representing the concept of DECEPTION is presented in the form of a frame consisting of slots, subslots, and components. First of all, we tried to analyze and diffrentiate the concept (meaning) of deception. To indicate the concept of deception a model of cognitive-semantic analysis of phraseological units which can be used in the study of other groups of phraseological units was proposed and substantiated. The object of the study is English phraseological units denoting deception selected by the method of continuous sampling. The subject of the study is the cognitive characteristics of phraseological units denoting deception. The purpose set also considered the task to denote cognitive features of the concept of deception being represented by the phraseological units and denote the connection between the conceptual sphere of DECEPTION and other spheres that correspond to the concept chosen.

Будучи складним переплетінням інтенціональних, когнітивних і моральних аспектів, обман супроводжує людську комунікацію і реалізується в ній. Обман як концепт є складником концептуальної картини світу, а мовні, зокрема фразеологічні, засоби об’єктивації цього концепту створюють мовну картину світу. Актуальність теми дослідження пояснюється, по-перше, великою значущістю концепту ОБМАН, об’єктивованого аналізованими фразеологічними одиницями, для англомовної спільноти, по-друге, відповідністю провідним напрямам сучасних лінгвістичних досліджень, по-третє, необхідністю виявлення когнітивного підґрунтя фразеологічних одиниць (ФО) на позначення обману для реконструкції концептуальної та мовної картин світу. Представлена стаття присвячена аналізу фразеологічних одиниць на позначення обману у когнітивному аспекті. Насамперед ми спробували проаналізувати та диференціювати поняття обману. Було систематизовано корпус фразеологізмів, які позначають обман, та виявлено специфіку фразеологічних одиниць на позначення обману в когнітивному аспекті. Аналіз фразеологічних одиниць на позначення обману представлений у вигляді фрейму, що складається зі слотів, підслотів та компонентів. Запропоновано та обґрунтовано модель когнітивно-семантичного аналізу фразеологізмів на позначення обману, яка може бути використана для вивчення інших груп фразеологізмів. Об’єктом дослідження виступають англійські ФО на позначення обману, дібрані із фразеологічних словників методом суцільної вибірки. Предметом дослідження є когнітивні особливості ФО на позначення обману, які реалізуються у фразеологічному значенні. Поставлена мета також зумовила завдання виявити когнітивні особливості обману, репрезентовані англійськими ФО, та встановити зв’язок концептуальної сфери (КС) ОБМАН з іншими сферами, які слугували джерелом для цієї КС.
Англійські фразеологічні одиниці на позначення обману у когнітивному аспекті
Keywords: cognitive linguistics; phraseological unit; concept; deception; cognitive aspect; frame; slot; subslot; когнітивна лінгвістика; фразеологічна одиниця; концепт; обман; когнітивний аспект; фрейм; слот; підслот